AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY IN NINTH GRADE STUDENTS OF MTS ILHAM PALEMBANG - Despita Despita (Journal of English Education, Literature and Linguistics, 2022)
Speaking is the action of convey information or expressing the idea and feelings in spoken English. This research explained about analysis the students’ speaking anxiety in ninth grade students of MTs Ilham Palembang. This research used qualitative research method, The researcher chose the ninth grade class which consists 68 students. In collecting the data, the researcher used observation, interview and questionnaire. The researcher used three major phases of the data analysis, they were: data reduction, data display and conclusion drawing verification. From the data analysis, the researcher found some conclusion of students’ speaking anxiety at the ninth grade as follows: first, researcher found that students’ speaking anxiety factor were: felt self-prediction toward fear, irrational faith, over sensitivity toward threat, the sensitivity of anxiety, wrong attribution body signal, low self-efficacy. Second, the causes of students’ speaking anxiety that student’ were unconfident to speak English, fear to make mistakes when speaking, anxiety when teacher asked to speak up, and shy to perform in front of class.